Persepsi Akademisi Bidang Lanskap Terhadap Objek Wisata Coban Talun di Kota Batu - Wiwin Seputri Kariam; Irawan Setyabudi (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2022)
ABSTRACT Batu City is one of the cities in East Java Province. One of the natural tourism potentials in Batu City is Coban Talun. Coban Talun is located in Wonorejo Hamlet, Tulungrejo Village, Bumiaji District, Batu City, East Java Province. Coban Talun is one of the natural tourism and artificial tourism that attracts many visitors. Coban Talun is managed by Perhutani and in collaboration with the private sector makes Coban Talun crowded with additional facilities and infrastructure. Coban Talun has rides consisting of waterfalls, flower gardens, photo spots, dams, pine pedestals, wooden bridges, Pagupon Camp, Apache Camp, and Omah Triangle. The development of Coban Talun in Batu City has a positive impact on the surrounding community by creating economic value, creating jobs, and increasing people's income. In addition, the development of Coban Talun can be a tourist attraction to Batu City. Views, opinions, and interpretations from various parties can support the development of Coban Talun through an analysis of perceptions of landscape quality, landscape potential, circulation, comfort, and attractiveness. Based on direct observation, visitors who come to Coban Talun are academics from Malang City, Malang Regency, and Batu City. This is also supported by data on Coban Talun's 16,575 visitors (City of Batu in Figures 2021). Perception is the way each individual can interpret an object differently depending on the point of view of each individual. The results of the study prove the perception of academics in the landscape field towards Coban Talun tourism objects in the city of Batu with the determination of 50 respondents using random sampling methods and data processing using the Likert scale method stating that the attractiveness of tourism objects in Coban Talun is very good with a total score of 2,027 and a maximum score of 2,500. with a percentage of 81.08%. While the accessibility of 50 respondents obtained 361 total scores with 500 total scores maximum with a percentage of 72.2% being in good criteria. While the facilities are in good criteria with a total score of 965 and a maximum score of 1,250 with a percentage of 77.2%. Keyword:perception, academics, landscap, coban talun